Stakeholders’ Perspectives on the Effectiveness of the Mid-Day Meal Program in Nepal - Pokhrel, Mahesh; Aryal, Bhagwan; Acharya, Devaraj; Sharma, Tribhuwon (HPE Forum, 2025)
The mid-day meal (MDM) program is vital in improving nutritional status and academic outcomes, particularly among basic school students from economically needy backgrounds. The MDM program provides nutritious meals to enhance school attendance, concentration on learning, class activities, and overall academic performance. This study synthesizes data from 2015 to 2024 regarding stakeholders' perspectives on the effectiveness of the MDM program, analyzing 18 academic research papers, policy documents, and reports accessed through Google Scholar, Research Gate, and Nepali institutional repositories. These sources were assessed on relevance keywords, publication, and methodological thoroughness, including a thematic analysis to identify key themes and gaps in the related literature. It revealed an enhancement in student educational participation, improving nutritional status and community engagement, fostering ownership, promoting social equity, health awareness and education, and increasing school attendance due to the Nepal MDM program. Yet some ongoing challenges such as food quality and nutritional standards, hygiene concerns, infrastructure challenges, stakeholder engagement, funding limitations, policy and implementation gaps, stakeholder collaboration, local food integration and strong monitoring to optimize program effectiveness and sustainability appear to be lacking. Despite their substantial benefits in enhancing student nutrition and educational outcomes, MDM programs face challenges such as the quality of food being served, hygiene, funding, and infrastructure deficiencies in Nepal. Strategic stakeholder collaboration, improved school facilities, and sustainable practices are essential for maximizing the program's long-term impact of these initiatives. This study contributes to a broader understanding based on stakeholders’ perspectives, linking pathways for future research, policy development, and effective program implementation of the MDM program in Nepal.